2002
DOI: 10.1191/0269216302pm586oa
|View full text |Cite
|
Sign up to set email alerts
|

Clinical nurse specialists in palliative care. Part 3. Issues for the Macmillan Nurse role

Abstract: The remit and boundaries of the Macmillan Nursing role in the UK have been called into question recently by a number of policy-driven changes. The rapid appointment of tumour site-specific nurses and the development of posts for palliative medicine, stemming originally from the Calman-Hine recommendations for reorganizing cancer services, have created unparalleled challenges of adaptation to new working practices and procedures. The extent to which Macmillan Nurses are adapting to these new demands was address… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 8 publications
1
36
0
Order By: Relevance
“…The nursing staff were uncertain of their confidence to work as part of a cancer care team. The latter is unsurprising as role ambiguity and conflict between nurses, doctors and other health care professionals have been topical within the field of cancer care (Seymour et al, 2002). This lack of clarity have sometimes been perceived as detrimental to patient care and management of symptoms (Sasahara et al, 2003).…”
Section: Engagement In Cancer Carementioning
confidence: 99%
See 1 more Smart Citation
“…The nursing staff were uncertain of their confidence to work as part of a cancer care team. The latter is unsurprising as role ambiguity and conflict between nurses, doctors and other health care professionals have been topical within the field of cancer care (Seymour et al, 2002). This lack of clarity have sometimes been perceived as detrimental to patient care and management of symptoms (Sasahara et al, 2003).…”
Section: Engagement In Cancer Carementioning
confidence: 99%
“…However the focus lies predominantly on the education and training of doctors and nurses (DOH, 2000a, b;Llamas et al, 2001;RCN, 2003) and to a lesser extent, other professionals such as social workers, physiotherapists and occupational therapists who make up the multiprofessional team, frequently perceived as key to the delivery of quality cancer care. Moreover, there is evidence to suggest that successful team working remains hindered by confusion over the skills and knowledge of different health care professions (Newall and Matthew, 1997;Bliss et al, 2000;Seymour et al, 2002;Sasahara et al, 2003).…”
Section: Preparation Of Health Care Professionals In Cancer Carementioning
confidence: 99%
“…Ideally, a doctor or nurse would be nominated for special responsibility for urology, joining daily ward rounds and sitting in on certain clinics. There is also clearly scope for attachment of a Macmillan nurse to the urology service [5] , and this is presently available in some hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…A review of these roles in 2002 found that as a result of changing models of cancer care and the rapid introduction of new nursing roles, there was a need to clarify the scope of the role in order to use their expertise most effectively (Seymour et al, 2002). Over recent years there has been an increasing interest in developing advance practice roles that focus more on clinical assessment, diagnostic reasoning and prescribing, traditionally the domain of medicine.…”
Section: Nursing and Palliative Care: A Critical Reflectionmentioning
confidence: 99%
“…However, in more recent times it has been argued that the dominance of the biomedical model has led to the overmedicalisation of death and dying and an erosion of this unique palliative care philosophy. (Clark, 2002) In order to be accepted as an authentic area of medicine in mainstream healthcare, the development of was inevitable, and this specialisation has been underpinned by a biomedical approach to health and illness (Clark, 2002). In a similar fashion, palliative care nursing has embraced a model of specialist practice and knowledge which has become distinct from other areas of nursing (A national professional development framework for palliative care nursing in Aotearoa New Zealand, 2014;Canning et al, 2005).…”
Section: Introductionmentioning
confidence: 99%